The Urgency of Legal Counseling by Land Deed Officials (PPAT) Regarding the Conversion of Agricultural Land Ownership for Tourism Businesses in Badung Regency - Ni Putu Nugraheni; I Nyoman Bagiastra (Warmadewa Press, 2026)
This study examines the urgency of legal counseling by PPAT in the practice of converting agricultural land for tourism businesses in Badung Regency. This issue shows a gap between das sollen (the social function of land and compliance with spatial planning as regulated in Law Number 5 of 1960 concerning Basic Agrarian Principles and Law Number 26 of 2007 concerning Spatial Planning) and das sein (the practice of massive, investment-oriented agricultural land conversion). The method used is normative juridical with a regulatory and conceptual approach. The results of the study show that although the authority of PPAT is limited to the creation of authentic deeds, the function of legal counseling is an inherent preventive responsibility to ensure compliance with spatial planning and guarantee legal certainty. Optimizing this preventive role is important in order to prevent administrative violations, disputes, and impacts on environmental sustainability and food security.